Environmental and individual characteristics associated with car use across Europe. (30th September 2020) - den Braver, N R; Kok, J G; Mackenbach, J D; Rutter, H; Oppert, J M; Compernolle, S; Twisk, J W R; Brug, J; Beulens, J W J; Lakerveld, J
Abstract: Background: This study aimed to determine which neighbourhood- and individual-level characteristics were associated with car driving in adults of five urban areas across Europe, and to determine the percentage of variance in car driving explained by characteristics at both levels. Methods: Neighbourhood environment characteristics potentially related to car use were identified from the literature. These characteristics were subsequently assessed using a Google Street View audit and available GIS databases, in 59 administrative residential neighbourhoods in five European urban areas. Car driving (min/week) and individual level characteristics were self-reported by study participants (analytic sample n = 4, 258). We used linear multilevel regression analyses to assess cross-sectional associations of individual and neighbourhood-level characteristics with weekly minutes of car driving, and assessed explained variance at each level and for the total model. Results: Higher residential density (β:-2.61, 95%CI: -4.99;-0.22) and higher land-use mix (β:-3.73, 95%CI: -5.61;-1.86) were significantly associated with fewer weekly minutes of car driving. At the individual level, higher age (β: 1.47, 95%CI: 0.60;2.33), male sex (β: 43.2, 95%CI:24.7; 61.7), being employed (β:80.1, 95%CI: 53.6; 106.5) and ≥3 person household composition (β: 47.4, 95%CI: 20.6;74.2) were associated with higher weekly minutes of car driving. Individual and neighbourhood characteristics contributed about equally to explained variance in minutes of weekly car driving, with 2% and 3% respectively. Conclusions: Residential density and land-use mix were consistently associated with minutes of weekly car driving, besides age, sex, employment and household composition. Although total explained variance was low, both individual- and neighbourhood-level characteristics were similarly important in their associations with car use in five European urban areas. Key messages: Both individual and neighbourhood level characteristics contributed equally to explained variation in car driving, across Europe. Higher residential density and land-use mix are consistently associated with lower care use.